2014
DOI: 10.1128/mbio.01331-14
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus A/Anhui/1/2013 (H7N9) Replicates Efficiently in the Upper and Lower Respiratory Tracts of Cynomolgus Macaques

Abstract: In March 2013, three fatal human cases of infection with influenza A virus (H7N9) were reported in China. Since then, human cases have been accumulating. Given the public health importance of this virus, we performed a pathogenicity study of the H7N9 virus in the cynomolgus macaque model, focusing on clinical aspects of disease, radiographic, histological, and gene expression profile changes in the upper and lower respiratory tracts, and changes in systemic cytokine and chemokine profiles during infection. Cyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…H7N9 subtype influenza A virus isolated from a human in 2013 caused viral pneumonia in cynomolgus macaques in the present study that was comparable to pneumonia reported previously in humans and other mammals (3,4,39). These results indicate that the H7N9 virus propagates sufficiently to induce respiratory symptoms in nonhuman primates and humans, although the virus has not obtained characteristics of sustained transmission among humans.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…H7N9 subtype influenza A virus isolated from a human in 2013 caused viral pneumonia in cynomolgus macaques in the present study that was comparable to pneumonia reported previously in humans and other mammals (3,4,39). These results indicate that the H7N9 virus propagates sufficiently to induce respiratory symptoms in nonhuman primates and humans, although the virus has not obtained characteristics of sustained transmission among humans.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, we used the same inoculation routes and virus dose of Anhui/1 as those used with other virus strains in previous studies to compare the pathogenicities of the viruses and the efficacies of vaccines and treatments (17,23,27). As a result, the pathogenicity of H7N9 influenza virus isolated in humans seems to be lower than that of H5N1 highly pathogenic avian influenza virus in primates and humans under an immunocompetent condition (4,17,39,60). Although the H7N9 vaccine in the present study conferred sufficient protective immunity to prevent severe viral pneumonia with virus inoculation through the trachea, we need to pay attention to the emergence and containment of resistant viruses during treatment with NA inhibitors even in immunocompetent patients, as confirmed in the present study using healthy macaques.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, this gene expression signature also occurs in the whole lung response to the infamous 1918 H1N1 virus, indicating that it may predict pathogenicity across different strains [15]. Experiments in cynomolgus macaques confirmed the validity of the pathways and molecules identified in the H7N9 mouse model [16].…”
mentioning
confidence: 49%
“…Gene expression profiles from H7N9-infected cells and tissues can be utilized to computationally identify small molecules and FDAapproved drugs that reverse the host gene expression patterns that may drive H7N9 pathogenesis. We have characterized the transcriptional response to H7N9 infection in human airway epithelial cells, BALB/c mice and cynomolgus macaques to identify host transcriptional signatures that distinguish H7N9 from other IAVs and are predictive of influenza pathogenicity across a range of influenza serotypes and strains [14][15][16]. Our host-directed approach to drug discovery has also identified drugs that could potentially be used to treat severe influenza caused by H7N9 and other pathogenic IAVs.…”
mentioning
confidence: 99%
“…In the most recent report to employ chest radiography to evaluate the extent of pulmonary disease, cynomolgus macaques were exposed to the avian H7N9 virus (De Wit et al, 2014). Interstitial infiltrates were detected in the lungs beginning on day 2 postexposure, and became diffuse by day 6 in most animals.…”
Section: Experimental Infections Of Nhps With Human Influenza VImentioning
confidence: 99%